Pengembangan Lembar Kerja Peserta Didik Berbasis Discovery Learning Dalam Meningkatkan Hasil Belajar Siswa Kelas XI Di SMA Negeri 1 Jogonalan - Endar Chrisdiyanto; Sri Wahyuningsih; Nidya Ferry Wulandari (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2023)
Education is one effort to improve the quality of human resources. This quality improvement is carried out through the process of learning activities. Indicators of the success of learning activities are learning outcomes. Student learning outcomes are still relatively low because teaching materials do not yet facilitate students in improving their learning outcomes. One of the teaching materials that can be developed to improve learning outcomes is LKPD. The research aims to improve student learning outcomes using discovery learning-based LKPD. This type of research is research and development (Research and Development) which consists of several main steps, namely: problem identification, data collection, product design, product improvement. Research was carried out on class XI students at SMA Negeri 1 Jogonalan, Klaten Regency. The analysis technique used is descriptive quantitative. The results obtained from this research are in the form of a product, namely a K-13 Student Worksheet based on Discovery Learning on Transformational Geometry material. The research results show that the feasibility of developing LKPD based on discovery learning as assessed by media experts is in the feasible category (0.81). and Thus it can be concluded that discovery learning-based LKPD can be used in the SMA Negeri 1 Jogonalan, Klaten Regency environment. The results of student learning using the essay test were 28 students (80%) who completed it by achieving a KKM score ≥ 75, and 7 students (20%) had not achieved the KKM score or had not yet completed it. Keywords: Keywords: LKPD, Discovery Learning, Learning Outcomes